KAMPUNG BAJO PRENEUR: EMPOWERMENT ANAK MUDA SUKU BAJO MELALUI EDUKASI ENTREPRENEUR - wahyuni, syahri; masitah, Masitah; wi, De; Daena, Suwardi (MALLOMO: Journal of Community Service, 2023)
Developing a person's character and entrepreneurship is very important, because interest always stimulates concentration of thought, creates joy in entrepreneurship and increases a person's entrepreneurial abilities. The aim of this activity is to promote entrepreneurial characteristics and culture and improve the skills of Bajo youth in the exploitation of the natural resources of their environment to turn them into goods with high use value and greater economic value. . This activity was carried out using the method of direct presentation of the material and continued with direct discussion and practice of making the products. The result of this activity is that the youth of the Bajo tribe already have an entrepreneurial spirit and are capable of exploiting the natural resources of their environment, as evidenced by their ability to produce processed fish food products. The objective of this activity was achieved, namely the formation of qualities and entrepreneurship among Bajo youth, as well as the skills of Bajo youth to use the resources of their environment in high value goods. use and higher economic value.